2023
DOI: 10.5530/pj.2023.15.91
|View full text |Cite
|
Sign up to set email alerts
|

Model Prediction of Potential Disease Effects from PM2.5 Emission Among School Children in Coming 30 years in South Tangerang

Ernyasih Ernyasih,
Anwar Mallongi,
Anwar Daud
et al.

Abstract: Background:The largest global environmental health risk factor is the ambient of air pollution, that largely attributed to transportation emissions. One of the main causes of PM 2.5 emissions is thought to be onroad transportation. PM 2.5 has an impact on health, especially on children that relate to the respiratory system such as asthma, lung cancer, and decreased intelligence. Objective: The research objective was to predict the risk potential disease due to PM 2.5 in children from vehicle emissions in South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It could need more treatment and proper upkeep to guarantee that the water is safe to consume due to many sources of pollutants including from air and the communities behavior relate to water source. 22,23 The use of rainwater for drinking water has various advantages for the environment. To name a few, these are: lessen the strain on water systems Rainwater collection and use can lessen the strain on municipal water systems by lowering demand on them.This can be particularly significant in regions with scarce water resources or high water demand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could need more treatment and proper upkeep to guarantee that the water is safe to consume due to many sources of pollutants including from air and the communities behavior relate to water source. 22,23 The use of rainwater for drinking water has various advantages for the environment. To name a few, these are: lessen the strain on water systems Rainwater collection and use can lessen the strain on municipal water systems by lowering demand on them.This can be particularly significant in regions with scarce water resources or high water demand.…”
Section: Discussionmentioning
confidence: 99%
“…Preserve local watersheds: By lowering the quantity of contaminants that enter nearby waterways and the amount of stormwater runoff, collecting and using rainwater can help preserve local watersheds. [23][24][25][26] This can help to improve water quality and protect aquatic ecosystems. Maintain healthy soils: Rainwater is free of chemicals and salts that are typical of treated water, which can help to maintain healthy soils.…”
Section: Discussionmentioning
confidence: 99%
“…Durian skin antibacterial tests conducted by Anggraeni and Anam, 201629 and Ravichandran et al, 202023 found that durian skin extract can be used as an antibacterial for human pathogens such as Escherichia coli and Staphylococcus aureus bacteria. There was inhibition of the growth of Eschercia Coli and Stapilococus Aureus bacteria on durian skin according to the results of research conducted by R. Calyptranti et al (2022)37,56 and Muawanah, et al, 201912 .…”
mentioning
confidence: 81%
“…This is in line with research (Tuharea, 2022) with a value of Exp(B)=17.274, which shows that families with poor economic status have a 17 times greater risk of toddlers becoming stunted compared to families with sufficient economic status. A good family economic status makes it easier for parents to obtain health services, learning or meeting other needs for their toddlers, (Hilda et al, 2023;Parellangi et al, 2023, Ernyasih et al, 2023 Research (Sutriyawan et al, 2020) also shows a value of Exp(B)=2.065, which means that basic socio-economic levels have a 2 times greater risk of experiencing stunting. These results are in line with research (Rufaida et al, 2020) which shows that low family income provides a 2,344 times risk for toddlers experiencing stunting.…”
Section: Relationship Between Parental Income and Incidence Of Stuntingmentioning
confidence: 99%